2021
DOI: 10.1016/j.apcatb.2020.119417
|View full text |Cite
|
Sign up to set email alerts
|

One-pot prepared mesoporous silica SBA-15-like monoliths with embedded Ni particles as selective and stable catalysts for methane dry reforming

Abstract: Ni@SBA-15 monoliths with up to 5 wt.% of Ni were successfully synthetized by means of an original and easy one-pot sol-gel method. Transmission Electron Microscopy (TEM), X-ray Photoelectron Spectroscopy (XPS), Temperature-Programmed Reduction (TPR), Pair Distribution Function (PDF) and X-Ray Diffraction (XRD) were used for the structural characterization of the samples. After H2-reduction, those solids exhibited small Ni 0 particles (between 1-3 nm) highly dispersed (one of the highest dispersion reported in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(38 citation statements)
references
References 50 publications
0
36
2
Order By: Relevance
“…It was reported that the crystallite size of Ni was vital to resistance to coking in the DRM reaction . The catalyst with a smaller Ni crystallite usually exhibited better resistance to coking. ,, Particularly, coke deposition tended to be significantly suppressed when the size of nickel nanoparticles was below 5 nm. , However, it was surprising that the Ni/(NA-Al 2 O 3 ) catalyst with a Ni nanoparticle size of 18.0 nm showed superior resistance to coking. To elucidate the reason of resistance to coking of the Ni/(NA-Al 2 O 3 ) catalyst, Ni/(NA-Al 2 O 3 ) and Ni/(Al 2 O 3 -Sigma) catalysts were used as research objects to conduct the following experiments, such as CH 4 -TPSR, CO 2 -TPSR, FT-IR, and in situ DRIFTS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the crystallite size of Ni was vital to resistance to coking in the DRM reaction . The catalyst with a smaller Ni crystallite usually exhibited better resistance to coking. ,, Particularly, coke deposition tended to be significantly suppressed when the size of nickel nanoparticles was below 5 nm. , However, it was surprising that the Ni/(NA-Al 2 O 3 ) catalyst with a Ni nanoparticle size of 18.0 nm showed superior resistance to coking. To elucidate the reason of resistance to coking of the Ni/(NA-Al 2 O 3 ) catalyst, Ni/(NA-Al 2 O 3 ) and Ni/(Al 2 O 3 -Sigma) catalysts were used as research objects to conduct the following experiments, such as CH 4 -TPSR, CO 2 -TPSR, FT-IR, and in situ DRIFTS.…”
Section: Resultsmentioning
confidence: 99%
“…44 The catalyst with a smaller Ni crystallite usually exhibited better resistance to coking. 15,45,46 Particularly, coke deposition tended to be significantly suppressed when the size of nickel nanoparticles was below 5 nm. 47,48 Additionally, as shown in Figure 10C, the ratio of surface −OH groups of the Ni/(NA-Al 2 O 3 )-activated catalyst was greater than that of the reduced Ni/(Al 2 O 3 -Sigma) catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…The resulting PDF can been referred to as difference (or differential) PDF (d-PDF) [9]. This approach has been applied to a vast variety of supported catalysts [31,47,[52][53][54][55][56][57][58][59][60][61][62][63][64] . For example, d-PDF analysis allowed to characterize in detail the supported phases in gallium oxide-based catalysts for propane dehydrogenation (PDH) [31].…”
Section: Pdf Of Supported Nanoparticles Catalysts -When Differences M...mentioning
confidence: 99%
“…9 In the case of the "one-pot" strategy (or pre-synthesis method), the silicon source is mixed with the precursor of the active composition, which then both interact with the template to co-assemble into a porous framework. [10][11][12] This method has the advantage of being a simple operation and the formation of an atomic-scale mixture of active sites in the porous materials, while the additional heteroatom in the framework may destroy the ordered mesoporous structure, leading to further collapses during calcination. The "loading" strategy (or post-synthesis method) mainly involves the preparation of a stable mesoporous silica matrix, followed by its loading with the active composition.…”
Section: Introductionmentioning
confidence: 99%